Bryde’s Whale (Balaenoptera edeni brydei, Artiodactyla: Balaenopteridae) aggregation area in the Gulf of Chiriqui, Panama - Rasmussen, Kristin (2023)
Introduction: Even though they occur worldwide in tropical and subtropical waters, Bryde’s whales (Balaenoptera edeni) are one of the most enigmatic of all the balaenopterid species. Previous research has reported the presence of Bryde’s whales off the Pacific coast of Panama, but little is known about their behaviors, abundance, and distribution in these waters. Objective: We report on an area in the Gulf of Chiriqui, Panama, where Bryde’s whales have regularly been sighted. Methods: We conducted small-boat surveys for marine mammals in the Gulf of Chiriqui between 2001 and 2022, during both the austral (26 300 km) and boreal (4 700 km) winter seasons. Results: We made 25 sightings of 33 Bryde’s whales. Sightings were made in nine of the years surveyed, and most were in the austral winter season (92 %). Most sightings were of one animal (80 %), and one sighting was of a mother-calf-escort trio. The aggregation area appears near the Contreras Islands, where most sightings (84 %) were made. We have photo-identified 14 individual whales using the dorsal fin. One individual has been sighted over two years (2014 and 2015), while the remaining have been documented only once. No photographic matches have been made to other areas. Conclusions: The persistent use of this aggregation area could indicate it is used for foraging, and the presence of a calf may indicate the area is also used for reproduction. The one inter-annual resight suggests this area may be used repeatedly by some of the same animals. Further research is needed off Panama to better understand this population of Bryde’s whales, its conservation status, and its relationship to the broader eastern tropical Pacific populations. Expanding the marine protected areas in the Gulf of Chiriqui may be warranted in order to protect this aggregation area.